Humanitarian Law Perspective on the Protection of the Rights of Children in Armed Conflicts - Hetharie, Yared; Hetharie, Yosia (Law Research Review Quarterly, 2020)
Children are often victims of armed disputes, not only in the case they are trapped in situations of armed conflict but also children are often included directly as child soldiers, therefore children must be given protection to obtain their rights as a child in an armed dispute. Child protection is closely related to Human Rights that have been generally recognized by the international community. International legal instruments and national law have regulated the protection of children's rights. Countries that are involved in armed disputes and do not implement the provisions of humanitarian law in particular the protection of the rights of the child and are considered a war crime. This research is a legal research, which is a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues faced with the approach used is the legal approach, which is carried out by examining all laws and regulations relating to the legal issues being addressed. Countries that have not ratified the provisions of Humanitarian law, should be able to ratify the provisions of Humanitarian law regarding the protection of children from being directly involved in armed disputes, and implement them into armed disputes, and implement them into their respective national legislation each country.